Origin and geochemical implication of relatively high abundance of 17α (H)-diahopane in Yabulai basin, northwest China. (January 2019) - Jin, Xiao; Zhang, Zhihuan; Wu, Jia; Zhang, Chengjin; He, Yinan; Cao, Lei; Zheng, Ruihui; Meng, Weiqiu; Xia, Huanyu
Abstract: Relatively high abundance of 17α (H)-diahopane has been detected in source rock extracts in the Yabulai Basin, a lacustrine basin in northwest China. Gas chromatography-mass spectrometry (GC-MS), X-ray diffraction (XRD) and Field emission environment scanning electron microscope imaging (FE-ESEM) were used in combination with conventional geochemical parameters to unravel the enrichment mechanisms. Significant variations of 17α (H)-diahopane concentrations detected in the Xinhe Formation with similar maturity inferred that thermal evolution is not the unique factor inducing the compound generating. The sedimentation of samples rich in 17α (H)-diahopane usually occur under suboxic conditions. Results of mineralogy analysis suggested that samples with high content of 17α (H)-diahopane are rich in carbonate minerals (about 20 wt %), which might deposit in brackish-saline water depositional environment. Relatively high content of gammacerane is also consistent with the experimental results of XRD. Based on the viewpoint of Moldowan et al. (1991), the regular hopanes may be the precursor of the rearranged hopanes, with the Wagner-Meerwein rearrangement as the mechanism. In this reaction, the critical factor of methyl migration is the production of carbocation starting with dehydroxylation. We suggested a general scheme for the generation of 17α (H)-diahopane in this study. In lacustrine sediments, suboxic and brackish environment could catalyze the methyl migration accompanied by carbonate deposit. Its geochemical implication can be used to reconstruct lacustrine paleoenvironment and contribute to a better understanding on oil-oil correlation, oil-source rock correlation and petroleum system study. Highlights: A new scheme for 17α(H)-diahopane accumulation is proposed. The enrichment of 17α(H)-diahopane depends on the suboxic and brackish water environment. The model for enrichment of 17α(H)-diahopane mediates the contradictions of previous studies. The geochemical implications of 17α(H)-diahopane can be used to reconstruct lacustrine paleoenvironment.